Globalization and consumption: a case study of cool roofs as socio-environmental alternative - Anderson Luiz Godinho; Mairon Melo; Bruno de (Sustainability in Debate, 2020)
Globalization and consumer society are discussed in their environmental biases and with a transition between global and local scale. From experimental research, the effect of white roofs for temperature reduction in internal buildings at São Borja-RS is investigated. Practical experimentation makes use of habitats, with asbestos cement tiles. Graphs and statistical analysis were used in the study. It was verified that, in days of sun predominance, the habitations with white tile had 2 °C of temperature less than the gray tile, being this smaller in cases of cloudy or rainy weather. It has been estimated that, as a consequence of the lower temperature under ideal conditions, a white tile will result in a reduction about 4.4 kWh/year/m² in electric consumption with air conditioner, which translates into approximately R$ 2.00/year/m² (energy values at São Borja). Despite the appreciable reduction in average temperature, the financial return will be in the long term.